Dropout at the University: variables, its frames and policies of quality - Joan Rué Domingo (Universitat Politècnica de València, 2014)
The  paper  assumes  some  relevant  links connecting    both,    the    reflection    on student  dropout  and  quality  in  Higher Education.  The  assumed  frames  locate the  reflection  on  student  dropout  in  a wider  context  than  the  most  common studies   do.   That's   it;   the   influence exerted  by  the  tertiary  education  in  the student's   personal   development   and its  socio-economic  impact  on  the  local contexts  where  it  is  such  education  is developed. Beyond it, the paper analyzes some  of  the  more  relevant  data  related to  the  dropout  phenomena  and  some of  the  it  most  common  evaluations  on Higher Education in our country, besides considering  some  key  biases  detected in  studies  on  dropout.  To  deepen  the knowledge  of  this  phenomenon  means the development of high analytic criticism on previous studies and the frames they adopted in its analysis. Beyond the former analysis some feasible guidelines are proposed in order to build up better policies pointing at the dropout reduction in Higher Education. According to   such   proposal   some   key   concepts are  depicted  for  a  more  comprehensive approach   to   the   phenomena.   As   a closing  summary,  they  are  illuminated by  ten  basic  guidelines  aiming  at  the institutional intervention.